Identification of MAEA protein as a potential target for chemoresistance in osteosarcoma using bioinformatics and proteomic analysis - Zhang, Chen; Wang, Ruizhen; Yi, Xin; Wang, Wannian; Yang, Jing; Zhang, Lihua; Wang, Guibin; Wang, Wei (Frontiers in Oncology, 2025)
IntroductionOsteosarcoma (OS) is the most common bone tumor, characterized by a high incidence, rapid progression, and frequent metastases. The implementation of chemotherapy has made important progress, while the necrosis rate is limited and the survival rates remain unsatisfactory, therefore novel approaches are needed.MethodsWe used proteomic analysis to characterize the molecular landscape of patients exhibiting different levels of chemotherapy-induced necrosis.ResultsPatients with low necrosis rate (≤70%) showed distinct expression patterns, with significant upregulation of proteins involved in DNA replication, metabolism, and mitochondrial pathway. The Runx1-related signaling pathway was also identified as potentially involved in disease progression. Remarkably, Mitochondrial Ribosomal Protein L4 (MRPL4) and Macrophage Erythroblast Attacher, E3 Ubiquitin Ligase (MEMA) were identified as hub proteins in MEGENA analysis and the public database. By integrating with immunohistochemistry, the higher expression level was verified in samples of OS patients compared to those of healthy people. DiscussionOverall, our project improves the knowledge of the expression pattern with different necrosis rates of OS samples, and the findings of MRPL4 and MAEA indicate the potential role in chemoresistance and provide new targets for the therapeutic strategy for OS patients with a low necrosis rate.